STRUCTURAL CHANGES IN CAROTID AND FEMORAL ARTERIES IN PATIENTS WITH ARTERIAL HYPERTENSION DURING ANTIHYPERTENSIVE THERAPY WITH AMLODIPIN AND LIZINOPRIL - Danovskaya, E.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Сhanges in carotid and femoral arteries’ structure were studied in 100 patients (36 females amd 64 males) with arterial hypertension (AH) of I-II stages with mild, moderate and severe increase in arterial pressure (AP) in the age 49,69±13,15 under the effect of antihypertensive therapy with amlodipin, lizinopril and their combinations. Amlodipin, lizinopril and their combinations allow to control AP and regres in structural changes of carotid and femoral arteries. The most effective in AP control, in regression of structural changes of carotid and femoral arteries and in stabilization of atherosclerotic changes in carotid and femoral arteries IS the combination of amlodipin and lizinoprol.